Anti-TNF therapy for ulcerative colitis in Brazil: a comparative real-world national retrospective multicentric study from the Brazilian study group of IBD (GEDIIB) - Sassaki, Ligia Yukie [UNESP]; Magro, Daniela Oliveira; Saad-Hossne, Rogerio [UNESP]; Baima, Julio Pinheiro [UNESP]; Flores, Cristina; Correia, Lucianna Motta; Celani, Lívia Medeiros Soares; De Abreu Ferrari, Maria De Lourdes; Zacharias, Patricia; Feitosa, Marley Ribeiro; Dos Santos, Carlos Henrique Marques; De Freitas Lins Neto, Manoel Alvaro; et al. (Springer Nature, 2022)
Background: Anti-TNF therapy represented a landmark in medical treatment of ulcerative colitis (UC). There is lack of data on the efficacy and safety of these agents in Brazilian patients. The present study aimed to analyze rates of clinical and endoscopic remission comparatively, between adalimumab (ADA) and infliximab (IFX), in Brazilian patients with UC, and evaluate factors associated with clinical and endoscopic remission after 1 year of treatment. Methods: A national retrospective multicenter study (24 centers) was performed including patients with UC treated with anti-TNF therapy. Outcomes as clinical response and remission, endoscopic remission and secondary loss of response were measured in different time points of the follow-up. Baseline predictive factors of clinical and endoscopic remission at week 52 were evaluated using logistic regression model. Indirect comparisons among groups (ADA and IFX) were performed using Student's t, Pearson χ2 or Fisher's exact test when appropriated, and Kaplan Meier analysis. Results: Overall, 393 patients were included (ADA, n = 111; IFX, n = 282). The mean age was 41.86 ± 13.60 years, 61.58% were female, most patients had extensive colitis (62.40%) and 19.39% had previous exposure to a biological agent. Overall, clinical remission rate was 66.78%, 71.62% and 82.82% at weeks 8, 26 and 52, respectively. Remission rates were higher in the IFX group at weeks 26 (75.12% vs. 62.65%, p < 0.0001) and 52 (65.24% vs. 51.35%, p < 0.0001) when compared to ADA. According to Kaplan–Meier survival curve loss of response was less frequent in the Infliximab compared to Adalimumab group (p = 0.001). Overall, endoscopic remission was observed in 50% of patients at week 26 and in 65.98% at week 52, with no difference between the groups (p = 0.114). Colectomy was performed in 23 patients (5.99%). Age, non-prior exposure to biological therapy, use of IFX and endoscopic remission at week 26 were associated with clinical remission after 52 weeks. Variables associated with endoscopic remission were non-prior exposure to biological therapy, and clinical and endoscopic remission at week 26. Conclusions: IFX was associated with higher rates of clinical remission after 1 year in comparison to ADA. Non-prior exposure to biological therapy and early response to anti-TNF treatment were associated with higher rates of clinical and endoscopic remission.
Keywords: Adalimumab; Anti-TNF therapy; Clinical remission; Infliximab; Ulcerative colitis